FOSTERING ENTREPRENEURIAL MINDSETS: AN IMPACT ASSESSMENT OF A COMMUNITY-BASED ENTREPRENEURSHIP TRAINING PROGRAM FOR AT-RISK YOUTH - Thabo Mokoena; Josefa Flores; Andres Villanueva (Journal of Social Entrepreneurship and Creative Technology, 2026)
At-risk youth frequently encounter significant socio-economic obstacles, leading to high vulnerability to unemployment and social exclusion. Community-based entrepreneurship training programs are increasingly employed as vital interventions to foster self-sufficiency and build economic resilience. However, empirical evidence specifically quantifying their direct impact on the entrepreneurial mindset of this marginalized demographic remains limited. This research aims to assess the impact of a community-based entrepreneurship training program on fostering an entrepreneurial mindset—specifically entrepreneurial knowledge, self-confidence, and business intention—among at-risk youth. The study also explores the influential role of support factors like mentorship. A mixed-methods design was implemented. The quantitative phase utilized pre- and post-program surveys (N=100) to measure changes in key indicators. The qualitative phase included semi-structured interviews and focus group discussions to gain deeper insights into participant experiences and mindset shifts. Data was analyzed using paired t-tests and thematic analysis. Quantitative analysis showed a statistically significant increase across all measured indicators post-program. Entrepreneurial knowledge and confidence in starting a business saw dramatic increases, from 28% to 85% and 32% to 80% respectively. Furthermore, the intention to pursue entrepreneurship rose from 40% to 75%. Qualitative results underscored the crucial role of mentorship and peer networking in translating knowledge into actionable plans. The findings confirm that tailored community-based entrepreneurship training is highly effective and transformative, not only equipping at-risk youth with technical skills but also significantly empowering them psychologically to pursue entrepreneurship as a viable path for socio-economic mobility. This model warrants continued adoption and scalable implementation.